Evaluation of the effect of solar radiations on the growth of potential water borne and food borne pathogens during solar eclipse - S, Bhute Shrikant; P, Kukreja Girish; Shaikh, Talek; Katke, Prashant; Swami, Amar; More, Pratik; Nimje, Priyank (Journal of Ecobiotechnology, 2012)
<p style="margin-top: 0in; margin-right: 0in; margin-left: 0in; margin-bottom: 0.0001pt; text-align: justify; background-image: initial; background-attachment: initial; background-origin: initial; background-clip: initial; background-color: white; background-position: initial initial; background-repeat: initial initial;"> On new moon day when Moon passes between Earth and Sun solar eclipse can be seen from Earth. Although solar eclipse is a fascinating astronomical event, even in today’s fast, modern and civilized life, people have not been able to go away with superstitious beliefs related to outer space activity behind solar eclipse. These misbelieves eventually lead to great socio-economic losses due to discarding of cooked food and drinking water that was exposed to the eclipse directly or indirectly. So considering these misbelieves a study was conducted to see possible biological effects of solar radiations during solar eclipse on bacteria responsible for water borne and food borne diseases. E. coli, S. aureus, B. subtilis, S. typhi, which are known water and food borne pathogens, were exposed to solar radiations throughout the eclipse period. The effect of these radiations on the survival and growth rate of these organisms was assessed by suitable method and compared with that on control day. When such comparison was made, it indicated that there was no statistically significant effect of solar eclipse on the survival and the growth rate of these organisms. Hence, we insist dumping the cooked food or drinking water after solar eclipse should be avoided.